Novel Heteroaryl Selenocyanates and Diselenides as Potent Antileishmanial Agents - Baquedano, Ylenia (Antimicrob Agents Chemother, 2016)
A series of new selenocyanates and diselenides bearing interesting bioactive scaffolds (quinoline, quinoxaline, acridine, chromene, furane, isosazole, etc.) was synthesized, and their in vitro leishmanicidal activities against Leishmania infantum amastigotes along with their cytotoxicities in human THP-1 cells were determined. Interestingly, most tested compounds were active in the low micromolar range and led us to identify four lead compounds (1h, 2d, 2e, and 2f) with 50% effective dose (ED(50)) values ranging from 0.45 to 1.27 μM and selectivity indexes of >25 for all of them, much higher than those observed for the reference drugs. These active derivatives were evaluated against infected macrophages, and in order to gain preliminary knowledge about their possible mechanism of action, the inhibition of trypanothione reductase (TryR) was measured. Among these novel structures, compounds 1h (3,5-dimethyl-4-isoxazolyl selenocyanate) and 2d [3,3′-(diselenodiyldimethanediyl)bis(2-bromothiophene)] exhibited good association between TryR inhibitory activity and antileishmanial potency, pointing to 1h, for its excellent theoretical ADME (absorption, distribution, metabolism, and excretion) properties, as the most promising lead molecule for leishmancidal drug design.